Exploring the Impact of Functional Obstacles on Purchase Intention in Social Media Commerce: Evidence from Palestine - Amal Sulaiman; Fuadah Johari; Hartini Mohammad; Alaa Sulaiman (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2026)
Tier 4 (Non-Indexed Publication)